Significados do cuidado materno para adolescentes com filhos pré-termo internados em unidade neonatal - Soares, Fernanda de Moura (2016)
Introduction: Taking care of a newborn preterm amid its fragility, it is a delicate activity for any mother, especially for adolescent mothers who, in most cases, the emotional immaturity and inexperience can experience this moment as a very conflictive exercise. Objective: To analyze the meanings of maternal care for adolescents with preterm children admitted to the neonatal unit. Method: This is an analytical descriptive research with a qualitative approach, which was attended by twenty teenage mothers from 10 to 19, who were accompanying their preterm children admitted to a state reference hospital in Northeast Brazil. To obtain data were collecting information on secondary source and semi-structured interview. Data analysis was performed according to the Content Analysis, thematic modality. Results: The reports emerged three central themes: "The no possibility of maternal care", "Learning to care" and "Different experiences in the care of teenage mothers to newborn preterm." For teenage mothers each neonate inpatient unit allowed a differentiated understanding of care. The meanings of maternal care were expressed as feeling and practices involving the supply of the needs of infants, including breastfeeding and Kangaroo. Final considerations: Given the results, it is concluded that the construction of the meanings of maternal care for teenage mothers interviewed was influenced by the various environments of the Neonatal Unit (NICU UCINCo and UCINCa) and also the guidelines received by the neonatal team. In Unit Kangaroo where teenage mothers were closer to the child, empowerment, effectiveness of care and the recognition of being a mother could.